2020
DOI: 10.1177/1524838020925784
|View full text |Cite
|
Sign up to set email alerts
|

Positive Internal Experiences in PTSD Interventions: A Critical Review

Abstract: Evidence suggests that individuals with post-traumatic stress disorder (PTSD) symptoms exhibit deficits in positive internal experiences. This study critically reviewed empirically validated PTSD interventions to determine (1) whether positive memories, cognitions, and emotions were explicitly addressed and (2) the goals of focusing on these positive internal experiences. We selected 11 empirically validated PTSD interventions listed as “recommended/strongly recommended” in recently published reviews, reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…Prior research indicates that trauma‐exposed clients (Caldas, Jin, Dolan, Dranger, & Contractor, 2020) and trauma clinicians (Contractor, Caldas, Dolan, Banducci, & Jin, 2020) are willing and wish to therapeutically address positive memories in PTSD treatment. Consistent with this trend, a recent review indicated that positive memories and positive emotions are addressed as clinical targets and mechanisms in a few PTSD interventions (Contractor, Weiss, Forkus, & Keegan, in press). Further, there is considerable empirical support for memory‐focused interventions in reducing posttrauma outcomes (Hitchcock, Werner‐Seidler, Blackwell, & Dalgleish, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…Prior research indicates that trauma‐exposed clients (Caldas, Jin, Dolan, Dranger, & Contractor, 2020) and trauma clinicians (Contractor, Caldas, Dolan, Banducci, & Jin, 2020) are willing and wish to therapeutically address positive memories in PTSD treatment. Consistent with this trend, a recent review indicated that positive memories and positive emotions are addressed as clinical targets and mechanisms in a few PTSD interventions (Contractor, Weiss, Forkus, & Keegan, in press). Further, there is considerable empirical support for memory‐focused interventions in reducing posttrauma outcomes (Hitchcock, Werner‐Seidler, Blackwell, & Dalgleish, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…Third, this review may act as a stimulus to promote the implementation of the models that support the incorporation of positive memory techniques into conventional treatments (e.g., Contractor et al, 2018). Indeed, a recent review on PTSD interventions suggest that ∼50% of existing PTSD interventions incorporate positive memories in some manner (Contractor et al, 2020c). Finally, despite the transient effects associated with many of the reviewed techniques, the perceived non-aversive and pleasant nature of these interventions could facilitate the therapeutic process and the adherence, and strengthen the therapeutic alliance, which would optimise health benefits.…”
Section: Implications Limitations and Future Researchmentioning
confidence: 99%
“…Screening for positive emotion dysregulation among veterans presenting with PTSD symptoms might aid clinicians in better identifying individuals at high risk for STBs who may benefit from early intervention. Positive emotions (particularly their regulation) are often overlooked in clinical settings and trauma treatments (Contractor et al, 2020), despite emerging research on their role in cognitive‐behavioral treatment response (Taylor et al, 2017). This study adds to work focusing on how maladaptive responses to positive emotions underlie psychopathology (e.g., risky and health‐compromising behaviors; Weiss et al, 2018; Weiss, Schick, et al, 2019), thereby signifying a need for studies that assess the specific role of positive emotion dysregulation in treatment.…”
Section: Discussionmentioning
confidence: 99%